2012
DOI: 10.1080/1068316x.2011.613390
|View full text |Cite
|
Sign up to set email alerts
|

Attorney and lay beliefs about factors affecting jurors' perceptions of juvenile offender culpability

Abstract: We surveyed attorneys and college students to learn what factors they believe influence jurors' perceptions of juvenile offender culpability and then varied two of these factors in a simulated case to determine their actual effects on mock jurors' decisions. In Study 1, attorneys (N 030) and undergraduate mock jurors (N 047) believed that a juvenile offender's youthful (versus adult-like) appearance would mitigate jurors' ratings of juvenile culpability. Both groups believed that jurors' perceptions of juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Given that there are instances when jurors can recommend sentences (as cited in Camilletti & Scullin, 2012), these findings are relevant. For example, Warling and Peterson-Badali (2003) presented mock jurors with the trial of a male who stabbed and killed another male of the same age.…”
Section: Defendant Agementioning
confidence: 91%
See 1 more Smart Citation
“…Given that there are instances when jurors can recommend sentences (as cited in Camilletti & Scullin, 2012), these findings are relevant. For example, Warling and Peterson-Badali (2003) presented mock jurors with the trial of a male who stabbed and killed another male of the same age.…”
Section: Defendant Agementioning
confidence: 91%
“…Some feel that adolescents, particularly those under the age of 15 years, do not have the same criminal culpability and adjudicative competence as adults (see Kambam & Thompson, 2009;Schmidt, Reppucci, & Woolard, 2003), while others believe a "get tough" approach rendering strict and enduring consequences is most appropriate for juvenile offenders. Despite some protestors, juveniles are, at times, heard in adult courts and can be subjected to jury trials, where members of the public decide a verdict and, in some cases, recommend their sentence (as cited in Camilletti & Scullin, 2012). For this reason, it is very important to understand the factors that jurors consider when determining a verdict and sentencing in a juvenile offender case.…”
Section: Defendant Agementioning
confidence: 97%
“…No study has yet examined the influence of appearance on sentencing outcomes among youth in conflict with the law, yet similar results might be expected. Consistent with this idea, attorneys report that they believe youth will be viewed as less culpable when they have a more youthful, rather than mature, appearance (Camilletti & Scullin, 2012). In the context of cooffending, leaders perceived as less dominant or competent may subsequently receive a lighter sentence, despite their culpability in the crime relative to other group members.…”
Section: The Role Of Perceived Facial Appearance Among Youth Criminalmentioning
confidence: 98%
“…Other factors relevant to opinions about young offenders, such as youthful appearance and perceptions of their legal competencies have been investigated. For example, Camilletti and Scullin (2012) found that youthful appearance did not affect sentencing recommendations made by their sample of university students. Ghetti and Redlich (2001) found that their respondents believed that younger offenders are not as legally competent as older offenders but this did not affect opinions about appropriate sentences.…”
mentioning
confidence: 99%